Transformative learning through intercultural collaborative learning: A case study across university and primary school contexts - Horie, Miki; Liang, Xiaoxian; Azuma, Yuki (Journal of International Students, 2026)
This interpretive study focuses on the Rits Global Gateway Camp, an ICL program based on the Guiding Framework of Inclusive ICL. The framework connects local primary school students and university students with various cultural backgrounds studying in Japan. This study aims to explore and illustrate university students’ learning experiences throughout the program and to identify key facilitating factors that support inclusive ICL practices. Data were collected through in-depth interviews and complemented by contextual information from program observations. Through thematic analysis, we identified meaningful outcomes and transformative impacts of the program. This included strengthening participants’ self-efficacy and sense of agency.